PID-hysteresis voltage control technique for three phase induction motor (matlab simulink and arduino) - Hussian, Ammar Husaini (2014)
These phase induction motors are the most widely used electric motors in industry for converting electrical power into mechanical power. They are considered to be simple, rugged, robust, efficient and suitable for applications in harsh environment. However, their controllability remains a difficult task using conventional control method. The control difficulty is associated with high nonlinearity of the motor’s behavior, complexity of its analytical model and presence of interactive multivariable structures. Therefore, this project is proposed a design controller for three phase induction machines in high performance application. The PID Hysteresis controller is developed and simulates using MATLAB/Simulink software and downloads to Arduino where generates the PWM signal. The signals then send to gate driver of a three phase inverter to give a stable performance to the induction motor. The improvement of performance is by comparing the actual measured voltage of the motor with respect to their reference voltage. The difference is then corrected thus minimizing the voltage error. A simple hardware implementation of the PID Hysteresis voltage controller is designed and some simulation and experimental results are presented to demonstrate the validity of this approach.